2022
DOI: 10.3390/curroncol29060316
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Ablation of Hepatic Tumors at the Hepatocaval Confluence Using Irreversible Electroporation: A Preliminary Study

Abstract: Background: Tumors at the hepatocaval confluence are difficult to treat, either surgically or ablatively. Methods: A retrospective longitudinal study on patients ineligible for thermal ablation who underwent computed tomography-guided IRE for hepatic tumors at the hepatocaval confluence was conducted. Factors analyzed included patient and tumor characteristics, IRE procedure details, treatment-related complications, and prognosis. Results: Between 2017 and 2021, 21 patients at our institute received percutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…With the exception of 1 hepatic vein located near the lesion that was temporarily occluded and recovered within 1 month, all postcava remained perfused with PFS of 121 days and mOS of 451.5 days. These results suggest that IRE can safely and effectively treat HCC at the hepatocaval confluence 59 .…”
Section: Ire- Effectively Ablate Lesions In Dangerous Areasmentioning
confidence: 62%
“…With the exception of 1 hepatic vein located near the lesion that was temporarily occluded and recovered within 1 month, all postcava remained perfused with PFS of 121 days and mOS of 451.5 days. These results suggest that IRE can safely and effectively treat HCC at the hepatocaval confluence 59 .…”
Section: Ire- Effectively Ablate Lesions In Dangerous Areasmentioning
confidence: 62%
“…A range of complications can occur when delivering IRE to the liver. These vary from minor side effects such as mild pain and fever [ 90 ] to major complications such as hydrothorax [ 90 ], pneumothorax, and brachial plexus injuries [ 91 ]. The overall complication rate is 23.7% from collective data, with severe adverse events arising in 6.9% of cases [ 78 ].…”
Section: Irreversible Electroporationmentioning
confidence: 99%
“…After the first study by Thomson et al that described IRE ablation of liver tumors [18], several reports have suggested IRE as a useful ablation modality for hepatic malignancies adjacent to major blood vessels and/or the biliary tree, where thermal ablation techniques are associated with risk of complications and heating effect [19] [20,21], [22]. In a meta-analysis including nine studies and 300 patients undergoing IRE for liver tumors, major complications were reported in seven patients including four hepatic abscesses, one bile duct dilatation, one arrhythmia, and one portal vein thrombosis [23].…”
Section: Liver Cancermentioning
confidence: 99%